1990
DOI: 10.1108/eum0000000001086
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Measuring the Quality of Customer Service

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
186
1
14

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(202 citation statements)
references
References 22 publications
1
186
1
14
Order By: Relevance
“…In line with this, the quality of services can be defined as the difference between customer expectations and their actual experiences. If expectations are greater than performance, such quality is regarded as unsatisfactory which further affects the creation of dissatisfaction" (Parasuraman et al, 1985;Lewis, Mitchell, 1990).…”
Section: Quality Of Servicesmentioning
confidence: 99%
“…In line with this, the quality of services can be defined as the difference between customer expectations and their actual experiences. If expectations are greater than performance, such quality is regarded as unsatisfactory which further affects the creation of dissatisfaction" (Parasuraman et al, 1985;Lewis, Mitchell, 1990).…”
Section: Quality Of Servicesmentioning
confidence: 99%
“…service quality is trade-off between perceived benefits and perceived costs (Lovelock, 2000). In earlier studies, service quality has been referred as how service satisfies customers' needs or expectations (Lewis & Mitchell, 1990;Dotchin & Oakland, 1994). Parasuraman et al (1988) identified five dimensions of service quality: (1) Tangibles (facilities, equipment and appearance of staff) (2) Reliability (ability to perform the promised service dependably and accurately) (3) Responsiveness (willingness to help customers and provide prompt service) (4) Assurance (knowledge and courtesy of staff and their ability to convey trust and confidence); and (5) Empathy (caring, individualized attention the organization provides to its customers).…”
Section: Perceived Service Quality Customer Satisfaction and Perceivmentioning
confidence: 99%
“…In one of offered definitions which are usually applied in different sciences, it defines quality of offered services as a limitation of providing needs and stakeholder's expectations [8][9][10]. So, quality can be defined as the gap between client's expectations and received services and if expectations go beyond the function, the result would be client's dissatisfaction.…”
Section: Quality Definitionmentioning
confidence: 99%